Izokinetične meritve kolenskega sklepa kegljačev - Šimenko, Jožef (Šport (Ljubljana), 2016)
The purpose of the study was to present the peak torques and bilateral asymmetries of quadriceps and hamstring muscles in 9-pin bowlers. The study included 30 subjects (age: 23.43 +- 6.73 years, height: 173.85 +- 8.10 and weight: 71.47 +- 9.13 kg), which are all training 9-pin bowling for competition purposes (17 women and 13 men). From the sample 2 subjects were lefthanded and remaining 28 were right-handed. We performed isokinetic testing on a SMM dynamometer (Maribor, Slovenia), at a speed of 60 °/s in a concentric mode for quadriceps and hamstring muscles. Subject reached the values of the maximum torque in quadriceps left (L) = 218.3 +- 43.63 Nm (PTQ/BW 3.12 +- 0.7 Nm/kg), right (R) = 194.63 +- 52.27 Nm (PTQ/BW 2.78 +- 0.76 Nm/kg) and hamstrings L = 90.17 +- 25.29 Nm (PTQ/BW 0.85 % 0.26 Nm/kg), R = 116.37 +- 30.29 Nm (PTQ/BW 1.66 +- 0.46 Nm/ kg). Hamstring to quadriceps ratio (HQR) was on the left leg 0.41 +- 0.08 and on the right leg 0.61 +- 0.14. Bilateral asymmetry of quadriceps muscles was 18 +- 0.17 % and hamstrings 22 +- 0.08 %. The paired t test was conducted and statistically significant differences were found between the maximum torque of the L and R quadriceps p = 0.000, L and R hamstring p = 0.000, L and R quadriceps PT/BW p = 0.000, L and R hamstring PT/BW p = 0.000 and L and R HQR p = 0.000.
Keywords: asimetrije; asymmetries; izokinetika; kegljanje; mišična razmerja; muscle ratios; nine pin bowling; simetrije; sport; symmetries; šport